Verdelgen of verheffen? De evolutietheorie en de maakbaarheid van de mens - Bont, R. de (BMGN - Low Countries Historical Review, 2007)
To elevate or to exterminate? Evolution theory and the ‘Man’s ability to be transformed’ Around 1900, Belgian scientists from different disciplines were tempted to use the theory of evolution as a tool to make pronouncements about the ‘Man’s ability to be transformed’. Although some biologists did examine this issue, it was primarily sociologists, anthropologists, educationalists, criminologists and eugenicists who used biological language to tackle the question. In this article I argue that these commentators can be divided into two groups: the determinists and the voluntarists. The first tended to believe in an evolution that was determined by an insurmountable struggle for life. A larger group of voluntarists, however, believed human evolution could be adjusted by changing the milieu in which people lived. In spite of this difference, the two groups also had a lot in common. Both used biological terminology to argue for a new type of government, which was completely ‘objective’ and ‘scientific’. In this way, both became defenders of what can be described as a ‘depoliticization’ of politics. This article is part of the special issue ’De menselijke canon en de Lage Landen’.